Beban Ganda Perempuan Pekerja: Studi Kasus Sumber Stres pada Ibu yang Bekerja di Sektor Formal - Sandopart, Dewa Putu Yohanes Agata L. (PERSEPTIF: Jurnal Ilmu Sosial dan Humaniora, 2025)
This study explores the experiences of double burden and sources of stress among mothers employed in the formal sector in Indonesia. This qualitative case study involved six working mothers from three sectors, namely banking, education, and healthcare in Surabaya. Data were collected through in-depth interviews, observation, and document analysis, and analyzed using an interactive model. The findings reveal that the double burden experienced is multidimensional, including physical, emotional, and cognitive aspects. Maternal guilt emerges as the most dominant source of stress, surpassing formal work pressure. Stress manifestations include physical disturbances such as insomnia, migraines, and chronic fatigue, emotional disturbances such as anxiety, irritability, and helplessness, and behavioral changes such as decreased performance and social withdrawal. Stress is exacerbated by unequal distribution of domestic tasks with partners, pressure from in-laws, and lack of structural support in the workplace. The study identifies context-specific findings in Indonesia, including the presence of invisible mental load as an unseen yet energy-depleting cognitive burden, pressure from in-laws as a source of stress in collectivist culture, and the phenomenon of digital ibuism where social media reinforces unrealistic motherhood standards. The study recommends the need for gender-responsive employment policies, increased social support from partners and families, and psychological interventions to help working mothers manage maternal guilt and adopt more realistic parenting standards.